Sheep and goat nutrition on natural pastures in Kenya - Schwartz, H.J.; Said, A.N. (1986)
Comparative studies on adaptive strategies of Small East African Goats and Somali Blackhead Sheep to seasonal changes of forage quality and quantity on offer were carried out for 2 years on a semi-arid thornbush savannah. They included monitoring of pasture condition, performance recording, monitoring of health status, feeding behaviour observations, feed intake measurements, measurements of rumen volumes, feed passage rates, chemical analyses of forages, in-vivo digestibility trials (nylon-bag), morpho-metric analyses of rumen mucosa and carcass appraisal. A synopsis of all preliminary results obtained todate shows that the goat is a highly selective feeder with a lower dry matter intake of higher quality than the sheep. Feed passage rates in goats are faster, absorptive surfaces in the rumen are larger and short chain fatty acid absorption is faster than in sheep. Mature sheep show higher live weight changes in relation to seasonal forage supply than goats and can develop fat deposit during the growing sason, which account for up to 40% of the carcass weight. Fat deposits in goats rarely exceed 15%. This leads to the conclusion that goats rely mainly on selectivity and harvesting efficiency during seasonal food scarcity, whereas sheep rely more on the build-up of body reserves during the growing season.